Analisis Risk dan Return Saham Syariah - Ilkham Habibi; Muhammad Yafiz; Muhammad Syahbudi (Universitas Muhammadiyah Sumatera Utara, 2022)
At this time, investment has become one of the alternative financial management in the community. An investor buys a certain number of shares at this time with the hope of profiting from an increase in the price of the stock or a certain amount in the future, as an imbalance to risks associated with the investment. There are two distinct attributes attached, namely risk and time. The calculation and analysis can use the second level analysis or stock returns and also by analyzing the level of market risk or risk. This study aims to find out how the risk and return of Islamic stock in JII and ISSI compare. This research was conducted with a descriptive approach, while the object of research is companies that are members of JII and ISSI, using a different test related to whether there is a significant difference between sharia risk and return in JII and ISSI. The results of the study, it shows a high level of homogeneity or similarity, and it can be seen that the F value is 6.544 more with a significance level of 0.014 <0.05. The results of the independent sample t-test on the assumed equal variances for the risk variable show that the sig. (2-tailed) of 0.174 which is greater than 0.05. Then the results of the independent sample t-test on the assumed equal variances for the return variable show that the value of sig. (2-tailed) of 0.453 which is greater than 0.05. The conclusion that can be drawn is that there is no significant difference between the average returns and risks of Islamic stocks in JII and ISSI and the average returns and risks on the JII and ISSI stock indices are negative.